Study of prevalence of urinary tract infection in febrile children less than 5 years of age - T., Madhubalan; S., Chidambaranathan; E., Yazhini (International Journal of Contemporary Pediatrics, 2020)
Background: Fever is the most common reason for children under 5 years of age to visit the OPD. Unlike other foci of infection, only a little attention has been focused on the identification of UTI in febrile children. Quite often child receives antibiotics empirically without adequate evaluation of UTI. To determine the prevalence of UTI in all febrile children, from 2 months to 5years of age. Methods: The study included children admitted with bronchiolitis in between during the period of December 2018 to March 2019 at Department of Pediatrics, Raja Muthiah Medical College and Hospital. Totally 200 consecutive children from 2 months to 5 years admitted in the pediatric department Data related to age, sex, predisposing factors will be noted. Urine analysis and urine culture have to be done in all these patients. USG abdomen to be done in patients with culture positive UTI. Results: Among the 200 cases, the prevalence of UTI was higher among females (10%) than males (8%). Among the culture-positive cases UTI, an underlying focus of infection was present in 89% of cases and only 11% of cases did not have any foci. In this study, the % of cases with a duration of fever more than 5 days was 57, as compared to 43% in patients with fever less than 5 days. Among the 19 UTI cases, 5 of them presented with voiding difficulties and all the 5 cases had significant growth on culture. There was a significant association between UTI cases and voiding difficulties. Conclusions: Hence through this study, authors concluded that pyuria of >5 pus cells /HPF in the centrifuged sample should be considered as significant pyuria and hence further evaluation should be done in all these cases to promptly initiate antibiotic treatment and also to prevent morbidity and several long term sequelae.